Photostability studies on gemifloxacin and lomefloxacin in bulk powder and dosage forms - Tammam, Marwa Hosny (European Journal of Chemistry, 2014)
The photostability of gemifloxacin mesylate (GFLX) and lomefloxacin hydrochloride (LFLX) antibacterial agents in dilute aqueous solutions (bulk powder and dosage form) was studied by applying the International Conference on Harmonization (ICH) recommended conditions. The photodegradation processes were monitored by UV-Vis spectrophotometry and quantified by HPLC. The structures of degradation products in the aqueous solution have been deduced from LC-MS/MS. The GFLX and LFLX photodegradation kinetic rates were also determined. The photodegradation process for GFLX and LFLX solutions can be described as first order kinetic with rate constants 0.105 and 0.119 1/h, respectively, under the applied experimental conditions. The photodegradation rates of GFLX (0.119 1/h) and LFLX (0.0.157 1/h) in aqueous solutions were higher in dosage forms than bulk powder. Titanium dioxide cannot be used as an opacifier with these fluoroquinolone drugs because the rates of photodegradation of GFLX (0.0.161 1/h) and LFLX (0.0.164 1/h) were significantly enhanced by the addition of TiO2. The obtained results showed that these fluoroquinolone drugs are photolabile, thus these two drugs should be strictly protected from light during storage, administration and drug analysis.